ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA (IPM) MENGGUNAKAN METODE REGRESI LOGISTIK ORDINAL DAN REGRESI PROBIT ORDINAL (Studi Kasus Kabupaten/Kota di Jawa Tengah Tahun 2014) - Nurmalasari, Ratih; Ispriyanti, Dwi; Sudarno, Sudarno (Jurnal Gaussian, 2017)
Human Development Index (HDI) is one of the most important indicator to observe another dimensions of human development. The HDI is a measurement for achievement levels of the quality of human development. This study analyze HDI in the Districts/Cities of Central Java in 2014. The Central Java’s HDI data is categorized as low, medium, and high. The HDI presumed to be affected by many factors, such as high school participation rates, middle school graduates percentage, percentage of household with clean water access, numbers of health facility, open unemployment rate,and labour force participation rate. This study used the ordinal logistic regression and the ordinal probit regression as its statical analysis method. The result showed that factors affecting HDI in the Districts/Cities of Central Java in 2014 are percentage of household with clean water access and numbers of health facility. To evaluate the performance of ordinal logistic regression and the ordinal probit regression, researcher uses classification accuracy and AIC. Based on reasearch classification accuracy and AIC of each methods, the result showed that both the ordinal logistic regression and the ordinal probit regression has good result in analyzing factors affecting Human Development Index in the Districts/Cities of Central Java in 2014.Keywords: HDI, Ordinal Logistic Regression, Ordinal Probit Regression, Classification Accuracy, AIC